Keterampilan Numerasi Sains Mahasiswa dalam materi Fluida: Implementasi Lebih Lanjut Model Pembelajaran Inovatif RODE - Arief Ertha Kusuma; Suciati; Degi Alrinda Agustina; Nurul Mazidah; Pradini Agustina; Rusmansyah (Jurnal Penelitian Pendidikan IPA, 2026)
This study examines the application of the RODE (Read, Outline, Discussion, Evaluation) learning approach to improve pre-service teachers' science numeracy skills, aligned with the Sustainable Development Goal 4 (Quality Education). A quantitative study with a one-group pretest-posttest design was conducted with 37 PGSD FKIP UBT students. The assessment of scientific numeracy was conducted via a written examination featuring five distinct indicators related to fluid concepts. Given the non-normal distribution of the data (p < 0.05), the Wilcoxon signed-rank test was utilized. The results demonstrated a statistically significant improvement in skills post-intervention (p < 0.001), with the mean score increasing from 45.57 to 68.94. The computed N-gain score of 0.43 indicates a moderate enhancement in numeracy proficiency. The data indicate a positive trend across all measures; however, the one-group design suggests that these gains should be viewed as indicative improvements within the cohort rather than conclusive evidence of the RODE model's sole causality, as external factors were not controlled. In conclusion, the RODE model is an effective pedagogical framework for enhancing foundational numeracy skills in prospective educators, therefore supporting the formulation of sustainable teaching practices.